PSYCHOLOGICAL AND PEDAGOGICAL ASPECTS OF APPLICATION OF SCIENTIFICALLY BASED METHODS OF EDUCATIONAL COGNITIVE ACTIVITY (Pedagogy of Higher and Secondary Education, 2010)
The article deals with the question of forming the concepts « method» , «methodology method of teaching» in the pedagogical science. The author conciders the meaning of method as such mediated link of cognitive process which « saves » intelectual and creative offorts of the subject of cognitive activity in the penetrating process of one's own methodical experience into the previous generalizing experience and favours its conceptualization.